Pengaruh Content Marketing Pada Instagram @Skintificid Terhadap Brand Trust - Shelycia; Helga Liliani Cakra Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Consumers are now increasingly fond of making online beauty product transactions rather than buying directly offline. Therefore, social media is the right platform for Skintific to promote their brand. Social media, especially Instagram, is one of the most popular platforms and has many users in Indonesia. Through Instagram, Skintific implements a content marketing strategy. Considering that Skintific is a new brand in Indonesia, it is important for them to strengthen and maintain brand trust. Brand trust is an important factor that can create a positive image and influence consumer behavior in purchasing products. This study aims to determine whether content marketing on Instagram @skintificid has an effect on brand trust. The study used a quantitative method with a survey data collection technique. The survey was conducted by distributing questionnaires to 300 respondents. Data were analyzed using normality tests, hypothesis tests, and simple linear regression tests. The results showed that H0 was rejected and Ha was accepted, which means that content marketing on Instagram @skintificid had an effect on brand trust by 63.6%, while 36.4% was influenced by other factors outside this study. Although new in Indonesia, Skintific can build brand trust through content marketing on their Instagram. Based on the results of the questionnaire, Skintific is advised to use influencers in their content to provide information about the product, starting from how to use it, benefits, to product content.